Creativity as a interdisciplinary skill - Karademir, Ersin (Educar em Revista, 2021)
There are many theoretical and experimental studies on the concept of skill. In education, creativity is regarded as one of the most important skills with its complex dynamic nature. It is a high level skill that occurs interdisciplinarily whereby individuals produce new and useful product as a result of the interaction between skill, process and environment. Based on this notion, the first aim of this study is to provide a review of the development of theoretical and experimental studies, which describes different classifications and definitions of skills and its dynamic nature. The second aim of the study is to present a in-class practice to extent creativity of gifted students through teacher (researcher) observations and project products. The author performed a review of the recent literature (HU; ADEY, 2002; KARADEMIR, 2016, 2017) on primary-middle school / gifted students’ creativity. The result of the in-class practice study revealed that creativity skill can be developed by design and project based activities.